Método da busca harmônica aplicado na otimização de seções de pilares retangulares em concreto armado considerando custos econômicos e ambientais - Medeiros, Guilherme Fleith de (2012)
More economical structures with less environmental impact is an important goal to be attained in engineering design. Besides designing structures that support loads safety and preserve their functionality, this should be done as rational as possible. Furthermore, using optimization techniques in structural design can reduce the consumption of materials, whose extraction, manufacturing and transportation cause significant environmental damage. These techniques look for the best solution through a mathematical formulation, decreasing dependence related to intuition and experience of the engineer. This study aimed to optimize material saving and environmental costs of rectangular sections of concrete columns subjected to uniaxial flexural compression, using the Harmony Search method, which is a metaheuristic technique based in analogy to the process of obtaining the best musical harmony. Therefore, besides the consideration of materials costs in the process of structural optimization, numerical applications were made considering the environmental costs of each material, estimated from the Life Cycle Assessment. The dimensions of the concrete section, the quantity and size of the reinforcement and the characteristic strength of concrete constituted variables of the optimization problem. The columns were checked for the Ultimate Limit States and Serviceability Limit States, according to the precepts of ABNT NBR 6118 (2007). From the developed formulation, an algorithm written in Fortran was used in a series of numerical analysis to confirm the efficiency of the adopted procedure, as well as the algorithm of Harmony Search. Results were compared to those obtained by conventional design, as well as other optimization methods. In general, the optimization method of Harmony Search was efficient in the search for optimal solutions, as well as important considerations for the optimization of material and environmental costs of reinforced concrete columns were obtained from examples presented here.